Taxonomic study of Chinese species of the genus Macropsis (Hemiptera: Cicadellidae: Macropsinae): new species, new records, synonymy and replacement name - Li, Hu; Dai, Ren-Huai; Li, Zi-Zhong; Tishechkin, Dmitri Yu. (Zootaxa, 2012)
Seven new species of the genus Macropsis from China, M. adusta sp. nov., M. exteria sp. nov., M. hainanensis sp. nov., M. latiaedeagus sp. nov., M. lijiangensis sp. nov., M. robusta sp. nov. and M. tuberculiformis sp. nov. are described and illustrated; three species, M. emeljanovi Dubovskiy, 1966, M. illota (Horvath, 1899) and M. orientalis (Distant, 1916) are recorded from China for the first time; M. flavida Vilbaste, 1980 = M. recurvus Kuoh, 1981 syn. nov. and M. matsumurana (China, 1925) = M. pallidinota Kuoh, 1992 syn. nov. are redescribed and illustrated basing on the materials from China. A replacement name, M. zizhongi Li, Dai et Li, nom. nov. for the junior homonym M. gracilis Li et Liang, 2005 (nec Dubovskiy, 1966) is established.